2016
DOI: 10.1021/acs.jpcb.5b10526
|View full text |Cite
|
Sign up to set email alerts
|

Chiral, J-Aggregate-Forming Dyes for Alternative Signal Modulation Mechanisms in Self-Immolative Enzyme-Activatable Optical Probes

Abstract: Enzyme-activatable optical probes are important for future advances in cancer imaging, but may easily suffer from low signal-to-background ratios unless not optimized. To address this shortcoming, numerous mechanisms to modulate the fluorescence signal have been explored. We report herein newly synthesized probes based on self-immolative linkers containing chiral J-aggregate-forming dyes. Signal modulation by formation of chiral J-aggregates is yet unexplored in optical enzyme probe design. The comprehensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In accordance with this, Hennig et al developed a new bioprobe containing a self-immolative linker and chiral J-aggregate-forming dyes. [35] Detailed characterization of the newly identified probes using fluorescence, absorption, CD, and time-resolved fluorescence spectroscopy revealed that the dye-dye and dye-protein interactions were not detected for the free dyes in the solution and enzyme, respectively. From the experimental results, it is clear that the lifetime of the probe is longer than that of the corresponding free dyes, which is probably due to the closer proximity of the self-immolative probe system and the hydrophobic microenvironment generated by the second dye.…”
Section: Aggregates Of Miscellaneous Fluorophoresmentioning
confidence: 99%
“…In accordance with this, Hennig et al developed a new bioprobe containing a self-immolative linker and chiral J-aggregate-forming dyes. [35] Detailed characterization of the newly identified probes using fluorescence, absorption, CD, and time-resolved fluorescence spectroscopy revealed that the dye-dye and dye-protein interactions were not detected for the free dyes in the solution and enzyme, respectively. From the experimental results, it is clear that the lifetime of the probe is longer than that of the corresponding free dyes, which is probably due to the closer proximity of the self-immolative probe system and the hydrophobic microenvironment generated by the second dye.…”
Section: Aggregates Of Miscellaneous Fluorophoresmentioning
confidence: 99%
“…The resulting solution was stirred under argon at room temperature overnight. The solvent was evaporated, and then the residue was taken up in dichloromethane; the organic phase was washed with a solution of K 2 CO 3 , water and brine; dried on MgSO 4 , filtered and concentrated in vacuo. The final carbamates were purified by HPLC using 80 to 90% gradient of CH 3 (1) and (2) tert-Butyl(2-((4,5-dimethoxy-2-nitrobenzyl)oxy)-5-methoxyphenyl) carbamate (7).…”
Section: General Proceduresmentioning
confidence: 99%
“…The heterogeneous mixture was allowed to warm at room temperature and stirred 1 h 30 min under argon. The excess of LiAlH 4 was neutralized with NH 4 Cl at 0°C, and then the suspension was filtered on Celite 535; the resulting filtrate was diluted with EtOAc and treated with 1 M HCl, water and brine; and finally dried on MgSO 4 , filtered and concentrated in vacuo. The crude product was purified by column chromatography on silica gel, giving the alcohol 18 as an off-white powder (479 mg, 94%); rf 0.…”
Section: General Proceduresmentioning
confidence: 99%
See 2 more Smart Citations